2020
DOI: 10.1108/gm-04-2019-0062
|View full text |Cite
|
Sign up to set email alerts
|

Women in the workforce

Abstract: Purpose While women perform as well as their male counterparts at work, women are drastically underrepresented in the onboarding process to senior leadership. The link between occupational self-efficacy and the role it may play in how men and women make decisions about work has not been done. The purpose of this study is to examine potential differences of occupational self-efficacy, career aspirations and work engagement between women and men. Design/methodology/approach Online surveys were created and sent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
43
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 135 publications
(301 reference statements)
9
43
0
2
Order By: Relevance
“…Following Coffman (2014), we ask participants to use a slider scale to indicate which gender, on average, knows more about each category in general. 7 This 4 At Ohio State, participants earned a $5 show-up fee plus an additional $1 for every point earned in the selected part. At Harvard, they earned a $10 show-up fee, $15 for completing the experiment, and an additional $0.25 for every point earned in the selected part.…”
Section: B Category Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following Coffman (2014), we ask participants to use a slider scale to indicate which gender, on average, knows more about each category in general. 7 This 4 At Ohio State, participants earned a $5 show-up fee plus an additional $1 for every point earned in the selected part. At Harvard, they earned a $10 show-up fee, $15 for completing the experiment, and an additional $0.25 for every point earned in the selected part.…”
Section: B Category Selectionmentioning
confidence: 99%
“…We follow this quiz and code one answer as being objectively "correct," though we note that this may be seen as a more subjective category than the others. 7 They use a sliding scale ranging from −1 to 1, where −1 means "women know more" and 1 means "men know more." Participants report Kardashians, Disney, art, cooking, emotion, and verbal as areas of female advantage measure offers a direct measurement of stereotypes that can be compared to the kernel of truth hypothesis.…”
Section: B Category Selectionmentioning
confidence: 99%
“…Meanwhile, to move career-wise, a candidate must demonstrate aspiration, be intentional, be open to new opportunities, and be 'visible' to get a 'seat at the table of leadership' (Selzer & Robles, 2019, p.120). Hartman & Barber (2020) in their research found no significant difference between men and women in terms of professional self-efficacy which is the indicator of career aspiration; still, men were found to be more career-oriented.…”
Section: Research Objectivesmentioning
confidence: 86%
“…It can happen, as an educator is a woman's job but a man's career (Limerick, 1999). While women climb the organizational ladder in femaledominated fields, men go to the top by 'glass elevator': once a man occupies a lower position, there is a mentor of the same gender who supervises the man (Williams, 1992;Hartman & Barber, 2020). The study conducted since 1996 across the continents in 48 female-dominated professions, e.g., preschool teacher (proportional rate 0.94), nurses (0.91), receptionist (0.81), males on average are reported to have exactly the same callback rate as female do (Birkelund, 2019).…”
Section: Research Objectivesmentioning
confidence: 99%
“…Despite equal rights and increased openness in the workplace over the preceding decades, issues surrounding women in the workplace and how they perform compared to their male counterparts continue to generate much discussion. A research paper by Hartman and Barber (2020) explores the differences between men and women in the workplace in relation to their self-efficacy, career aspirations, and engagement. The paper aims to uncover how men and women differ in these occupational characteristics, and more specifically whether self-efficacy has an impact on the career goals of women.…”
Section: Introductionmentioning
confidence: 99%